PAK GEREJA DAN PENDIDIKAN KELUARGA DENGAN PERILAKU PEMUDA KRISTEN - Nofedin Waruwu (The Way Jurnal Teologi dan Kependidikan, 2020)
The purpose of this research was to see whether there was a relationship between Christian Religious Education and Family Education with youth behavior. The instrument used was a questionnaire. The number of instrument items consisted of 30 items for variable X1, 30 items for variable X2, and 30 items for variable Y. Requirements for analysis showed that the data came from a population with normal and linear distribution. The results showed that there was a relationship between the variables of Christian Religious Education and Family Education with youth behavior, by displaying a double (R) of 0.593, and the coefficient of determination (R square) of 0.352 and the coefficient of multiple determination (Adjusted R square) of 0.317. This means that the contribution made by Church PAK (X1) and PAK Keluarga (X2) together with Christian youth behavior (Y) is 31.7% and the rest is from other factors. The conclusion of this study is that there is a positive relationship between Church PAK and Family PAK with Christian adolescent behavior.